Implementation of soft skills on Automotive Engineering practicum of state vocational high schools in West Lombok Regency - Aprian Firmansyah; Soeharto Soeharto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This research aims to reveal the implementation of soft skills in the expertise program of automotive workshop at vocational high schools (VHS) in West Lombok Regency in terms of (1) student condition and practicum lesson planning, and (2) level of soft skills in automotive technology practicum of VHS students. This research is quantitative research with a descriptive approach. The research population is all state vocational high schools (SVHS) of light vehicle technology in West Lombok. The sample is four vocational high schools with 84 grade XII students and four teachers established using the purposive sampling technique. The research finding shows that (1) the student condition in the implementation of soft skills is in a good category with the achievement percentage of 46.43% and the lesson plan condition is in a good category with the achievement percentage of 58.33%; (2) the achievement level of soft skill is in a good category with the achievement percentage of 49%.